The Influence of In-Shop Emotion on Repurchase Intention through Customer Satisfaction at Lotte Grosir Solo - Darpito, Surpiko; Alrafi, Krisnha; Probosari, Ninik; Satoto, Shinta; Liestyana, Yuli (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to analyze the direct influence of in-shop emotion on repurchase intention, as well as its indirect influence through the mediation of customer satisfaction and customer loyalty at Lotte Grosir Solo. This study falls under quantitative research, employing non-probability sampling with purposive sampling as the chosen method. The population comprises a portion of Lotte Grosir Solo consumers, with a required sample size of 100 respondents selected based on predetermined criteria. Data collection took place in February 2023 through questionnaires distributed via Google Forms. SmartPLS 3.2.9 was used as the data analysis method. The test results indicate that all three variables (predictor and two mediators) effectively explain the criterion construct. From the study, it was found that in-shop emotion has a positive but not significant direct influence on repurchase intention. However, in-shop emotion has a positive and significant influence on both mediations, and subsequently, both mediations have a positive and significant impact on repurchase intention. In conclusion, this research demonstrates that in-shop emotion indirectly, through its mediations, has a positive and significant impact on repurchase intention.